Tools and methods of databases optimization in Oracle Database 10g. Part 1 – tuning instance - Barczak, Andrzej; Zacharczuk, Dariusz; Pluta, Damian (Studia Informatica. System and information technology, 2019)
The purpose of this article is to show the various questions and issues of databases optimization, and learn methods to improve the performance of the database based on the Oracle 10g DBS. The following parts will present working of these mechanisms, obtained effects and estimation of the results.